EVALUASI DESAIN TERMAL KONDENSOR PLTN TIPE PWR MENGGUNAKAN PROGRAM SHELL AND TUBE HEAT EXCHANGER DESIGN - Steven Mangihut Darmawan; Steven Darmawan; Suroso Suroso (Program Studi Teknik Mesin Universitas Tarumanagara, 2017)
Abstract: The study was executed to get a quick calculation method for the design of equipment heat exchanger type shell and tube with a program shell and tube heat exchanger design. The purpose of this study was to obtain the results of the validation program shell and tube heat exchanger design of a condenser with power 4368.75 kW and the results of the evaluation program shell and tube heat exchanger design on the thermal design condensers nuclear power plant AP1000 PWR type. Input data into the program is done by inserting the parameters temperature, flow rate, physical properties and geometrical dimensions of the available designs of heat exchanger equipment specifications. Parameter for comparison of data can be obtained from the results of other calculations or experimental data. The results of comparison of the validation program shell and tube heat exchanger with condenser design calculations showed the highest difference found on Utube parameter equal to 1.3% lower than the design condition. This occurs because of differences in calculation between the program designed. The result evaluation of program shell and tube heat exchanger design toward the thermal design condensers nuclear power plant PWR type AP1000 obtained unknown parameters from the technical specifications.